Anacyclus pyrethrum extracts: examination of bioactive compounds and therapeutic implications through in vivo, in vitro, and in silico assays - Elhouda-Mekhadmi, Nour; Mlik, Randa; Abid, Asma; Adaika, Aicha; Bentahar, Assia; Ben Amour, Safia; Mouane, Aicha; Boussebaa, Walid; Ramdani, Messaoud; Ghemam Amara, Djilani; Victor Atoki, Ayomide; Sawicka, Barbara; et al. (Italian Journal of Food Science, 2024)
Anacyclus pyrethrum, a native Algerian medicinal plant, demonstrates notable therapeutic efficacy. The bioactive profile of the Anacyclus pyrethrum extract was examined using HPLC-UV-VIS, which showed a high concentration of phenolic compounds (33.46 ± 0.57 mg EAG/g EP) and flavonoids (11.08 ± 0.24 mg E Qu/g EP). The Anacyclus pyrethrum extract exhibited significant antioxidant activity in iron chelation (IC50 = 0.019 ± 0.0006 mg/ml) DPPH (IC50 = 0.142± 0.001 mg/ml), ABTS+ (IC50 = 0.079 ± 0.0005 mg/ml) and OH (IC50 = 0.845 ± 0.052mg/ml) radicals. Anti-inflammatory investigations were conducted using both in vitro and in silico methods. The in vitro testing involved evaluating the denaturation of egg albumin and BSA, while the in silico tests focused on measuring the effect of caffeic acid on the COX-2 protein. The anti-inflammatory capacity of the substance was similar to that of Aspirin, with a value of 76.1 ± 1.04% compared to Aspirin’s 81.11 ± 1.6%. Our extract exhibited a fatal dose (LD50) of 45.847 ± 1.661 mg/ml and showed significant antibacterial activity with minimum inhibitory concentrations (MICs) ranging from 2.5 to 27.5 mg/ml. The findings emphasize the wide range of medicinal uses of Anacyclus pyrethrum, underscoring its significance in both traditional and modern pharmacology.